2015
DOI: 10.1080/00103624.2015.1069311
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Soil Homeostasis under Exposure to Cadmium

Abstract: This study makes a pioneering attempt to analyze the neutralizing effects of algae extracts and basalt flour on cadmium-contaminated soil with the aim of restoring a healthy soil balance. Their effectiveness was compared with that of straw and compost.The following soil parameters were determined to evaluation of changes in a cadmiumcontaminated environment: dehydrogenases and catalase activity, population size of microorganisms. The influence of cadmium on the resistance of spring barley crops was evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In our experiment, colonies of microorganisms grew faster from wet than from air-dry soils, which is evidenced by higher CD values in the former group of soils (Table 4). This finding is particularly important because the more rapidly growing microorganisms there are in soil, the more easily fresh organic matter is degraded (Zaborowska et al 2015). However, such microorganisms are less stable in the environment than those which grow more slowly.…”
Section: Resultsmentioning
confidence: 99%
“…In our experiment, colonies of microorganisms grew faster from wet than from air-dry soils, which is evidenced by higher CD values in the former group of soils (Table 4). This finding is particularly important because the more rapidly growing microorganisms there are in soil, the more easily fresh organic matter is degraded (Zaborowska et al 2015). However, such microorganisms are less stable in the environment than those which grow more slowly.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers share the view that a decrease in the enzymatic activity of soils is a manifestation of abiotic stress caused by accumulated heavy metals in excessive amounts (Kucharski et al 2011 ; Wyszkowska et al 2013 ; Zaborowska et al 2015b ; Xian et al 2015 ). Dehydrogenases are considered the most sensitive parameters used to assess the effects of soil environment contamination (Gil-Sotres et al 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…Like in the case of eukaryotic microorganisms, toxic effects of heavy metals on cells of microorganisms depend on metal type and concentration, and species of cultivated plant [69][70][71]. In the present study, heavy metals elicited various effects on microorganisms tested.…”
Section: Sensitivity Of Soil Microorganisms To the Effects Of Ni 2+ ...mentioning
confidence: 57%
“…Our previous research [4] conducted with soil sown with Brassica napus demonstrated actinobacteria to be more resistant to the effects of Cd 2+ than Co 2+ and Ni 2+ . The diversified effects of heavy metals on microorganisms were also pinpointed by Zaborowska et al [69] and Giller et al [72]. In turn, in experiments carried out by Zaborowska et al [73] and Boros-Lajszner et al [74], the adverse effect of Co 2+ on the microbiome aggravated along with its increasing content in the soil.…”
Section: Sensitivity Of Soil Microorganisms To the Effects Of Ni 2+ ...mentioning
confidence: 82%